Effects of carbamide on sulfoaluminate cement paste for growing plants. (15th June 2016) - Huang, Qingliang; Zhou, Xiangming; Zhuang, Liping; Gong, Chenchen; Lu, Lingchao; Fu, Xinghua
Highlights: Carbamide delays the hydration of CSA cement and prevents the formation of AFt. Carbamide increases the fluidity and extends the setting time of CSA cement pastes. CSA cement hardened pastes with carbamide can release nitrogen nutrients. Abstract: To better understand the effects of carbamide on the properties of sulfoaluminate cement as potential matrix for eco-concrete suitable for growing plants, the fluidity, hydration heat evolution, setting time, compressive strength development, hydration products, pore characteristics and releasing characteristics of nitrogen nutrients of sulfoaluminate cement with carbamide were investigated. It was found that carbamide can reduce the water demand of sulfoaluminate cement. The fluidity increased from 80 to 149 mm with carbamide content increasing from 0.2 to 4.0 wt.%. Carbamide had noticeable retarding effect on the hydration of sulfoaluminate cement, especially on C3 S phase. The cumulated hydration heat of sulfoaluminate cement pastes without and with 4.0 wt.% carbamide was 329.5 J/g and 296.3 J/g, respectively. Carbamide retarded initial setting time of sulfoaluminate cement enabling it being able to meet the setting time requirement of GB20472-2006 (Chinese national standard for Sulfoaluminate cement). The early compressive strength of sulfoaluminate cement was low due to the retarding effect caused by carbamide and the production of NH3 increased the total porosity, but carbamide had limited effects on late age compressive strength of sulfoaluminate cement. Hardened sulfoaluminate cement pastes with carbamide can release nitrogen nutrients which is essential for growing plants. The amount of nitrogen nutrients released from sulfoaluminate cement paste with 2.0 wt.% carbamide cured for 56 days was 0.92 mg/cm 3, and the cumulative release rate was 75.0%. The presence of carbamide enables hardened cement paste being able to release nitrogen nutrients, suggesting that carbamide can mix with sulfoaluminate cement to produce eco-concrete and release nitrogen nutrients for growing plants.